Analisis Gaya Kepemimpinan dalam Meningkatkan Loyalitas dan Kepuasan Kerja Karyawan PT BPRS Haji Miskin Pandai Sikek - Sherli Rahmayola; Habibatur Ridhah (ARZUSIN, 2026)
Leadership style plays an important role in shaping employee loyalty and job satisfaction, particularly in Islamic financial institutions. Although organizational leadership has been widely studied, research that specifically analyzes the implementation of leadership styles in improving loyalty and job satisfaction at Sharia People’s Financing Banks (BPRS), especially in organizations with more than one leader who has different leadership characteristics, remains limited. This study aims to analyze leadership styles in improving employee loyalty and job satisfaction at PT BPRS Haji Miskin Pandai Sikek. This study used a qualitative approach with a descriptive field research design. The informants consisted of leaders and employees of PT BPRS Haji Miskin Pandai Sikek who were selected using purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and were then analyzed using an interactive analysis model that includes data reduction, data display, and conclusion drawing. The results show that the leadership style implemented is a combination of democratic, transformational, and authoritarian styles that contributes to the formation of employee loyalty through communication, motivation, and harmonious working relationships. However, job satisfaction has not yet been fully optimized because there are still obstacles in the bonus distribution system, task allocation, and information transparency. These findings contribute to the development of leadership studies in Islamic financial institutions and expand understanding of leadership implementation in improving loyalty and job satisfaction. The conclusion of this study emphasizes the importance of adaptive, communicative, and transparent leadership styles in strengthening loyalty and improving employee job satisfaction. The implications of this study can serve as input for BPRS management in developing leadership practices that are fairer, more open, and oriented toward employee welfare.